Fluid biomarkers in frontotemporal dementia: past, present and future. Issue 2 (13th November 2020) - Swift, Imogen Joanna; Sogorb-Esteve, Aitana; Heller, Carolin; Synofzik, Matthis; Otto, Markus; Graff, Caroline; Galimberti, Daniela; Todd, Emily; Heslegrave, Amanda J; van der Ende, Emma Louise; Van Swieten, John Cornelis; Zetterberg, Henrik; et al.
Abstract : The frontotemporal dementia (FTD) spectrum of neurodegenerative disorders includes a heterogeneous group of conditions. However, following on from a series of important molecular studies in the early 2000s, major advances have now been made in the understanding of the pathological and genetic underpinnings of the disease. In turn, alongside the development of novel methodologies for measuring proteins and other molecules in biological fluids, the last 10 years have seen a huge increase in biomarker studies within FTD. This recent past has focused on attempting to develop markers that will help differentiate FTD from other dementias (particularly Alzheimer's disease (AD)), as well as from non-neurodegenerative conditions such as primary psychiatric disorders. While cerebrospinal fluid, and more recently blood, markers of AD have been successfully developed, specific markers identifying primary tauopathies or TDP-43 proteinopathies are still lacking. More focus at the moment has been on non-specific markers of neurodegeneration, and in particular, multiple studies of neurofilament light chain have highlighted its importance as a diagnostic, prognostic and staging marker of FTD. As clinical trials get under way in specific genetic forms of FTD, measures of progranulin and dipeptide repeat proteins in biofluids have become important potential measures of therapeutic response. However, understanding of whether drugs restore cellular function will also be important, and studies of key pathophysiological processes, including neuroinflammation, lysosomal function and synaptic health, are also now becoming more common. There is much still to learn in the fluid biomarker field in FTD, but the creation of large multinational cohorts is facilitating better powered studies and will pave the way for larger omics studies, including proteomics, metabolomics and lipidomics, as well as investigations of multimodal biomarker combinations across fluids, brain imaging and other domains. Here we provide an overview of the past, present and future of fluid biomarkers within the FTD field.